WEBSITE SISTEM INFORMASI PEMETAAN BANGUNAN BERSEJARAH KOTA SERANG, PROVINSI BANTEN - Yenita Candra Sari; Ery Dewayani; Bagus Mulyawan (Fakultas Teknologi Informasi Universitas Tarumanagara, 2018)
Banten is located in Tatar Pasundan, which has many historical buildings. To overcome the limitations of the information historical buildings in Kota Serang, it was designed and built a system that can provide information on the presence of historical buildings in Kota Serang so that people can know more about the history, the events that occurred in these buildings.The methods used for collecting data are observation and interview. The research method used is SDLC (System Development Lyfe Cycle). The programming language used is PHP and PHPMyAdmin for database management.